Bookbinding History and Sacred Cows. (18th December 2020) - Pearson, David
Abstract: Book history has increasingly developed a cohesive view of the printing, selling, owning, reading and use of books, but bookbinding continues to struggle to find its place in the teaching and perception of the disciple. This is counter-intuitive, and a missed opportunity, in a world in which we talk so much about the book as a material object. This paper examines the reasons, and challenges many of the assumptions or beliefs that remain endemic in binding history. It offers examples of ways in which a different approach to binding studies is needed, while considering debates about the relative usefulness of methodologies based around decoration, or structure. It sets out a philosophy, or methodology, for the study of bindings in a book-historical context, with some basic questions which we should bring to any binding before us.